Pengaruh Rekrutmen terhadap Kinerja Pegawai Non-Medis di Rumah Sakit Umum Pindad Bandung - Fifit Hadiaty; Dinna Astriyana (Jurnal Sekretaris dan Administrasi Bisnis, 2019)
This research is aimed to find out the influence of recruitment toward the performance of the non-medical employee in Pindad General Hospital Bandung. We use quantitative method in this research, and the data collecting method we use observation, questionnaire, interview, documentation study and literature review. The number of population is ten respondents consisted of Head of Non-Medical Employee Affairs and Head of Non-Medical Employee Section, and sample use in this research is Saturation Sampling. The calcuration result of correlation test provides correlation coefficient as much as 0.531 which means that the level of relation strengh (correlation) is between 0.51-0.57 or strongly related. This study aims to determine the effect of recruitment on the performance of non-medical employees at Pindad Bandung General Hospital. The type of research used is quantitative methods and data collection techniques used are observation, questionnaires, interviews, study documentation and literature. The total population is 10 (ten) respondents, namely the head of affairs (Kaur) and the head of the field (Kabid) of non-medical employees, the entire population is sampled then the sampling technique uses saturated sampling. Based on the result of this research, we provide these suggestions : 1) Finding out the employee that has appropriate education level with the position needed, 2) Using the various media to display job vacancy advertisement, 3) Increasing the supervision in academic test, 4) Addition of employee in Human Capital for personnel and education training division. Keyword: Employee recruitment, performance, non-medical employee